2010
DOI: 10.3109/09638281003649920
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial well-being of parents of children with cerebral palsy: a comparison study

Abstract: These results suggest caring for a child with CP may put parents at risk from poor psychosocial well-being. Interventions to improve parental well-being are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 28 publications
8
56
1
8
Order By: Relevance
“…The results of this study are consistent with research demonstrating enhanced parenting stress in parents of children with CP [4][5][6][7]. Further, this study suggests that the theoretical framework of chronic sorrow theory may be useful in understanding the experiences of parents of children with CP [8][9][10][11].…”
Section: Discussionsupporting
confidence: 80%
“…The results of this study are consistent with research demonstrating enhanced parenting stress in parents of children with CP [4][5][6][7]. Further, this study suggests that the theoretical framework of chronic sorrow theory may be useful in understanding the experiences of parents of children with CP [8][9][10][11].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the physical, psychological, and total scores of WHOQOL-BREF TR and BDI of the caregivers of children with CP were statistically significantly correlated with their wards' GMFCS scores. Contrary to this, other previous studies have shown no significant correlations among caregivers' QoL, emotional stress, and the children's GMFCS levels [19,22]. However, our study showed coincident results with Basaran et al [24].…”
Section: Discussioncontrasting
confidence: 57%
“…In literature, the caregivers of children with severe clinical impairments, especially with regard to motor function, are more likely to have greater physical and mental distress than other caregivers [17][18][19][20][21]. In addition, caregivers' QoL was significantly affected by the motor function of children with CP in this study.…”
Section: Discussionmentioning
confidence: 47%
“…이상에서 살펴본 바와 같이, 뇌성마비 아동 어머니 대상의 국내외 연구들은 양육스트레스 [1,6,14,[17][18][19]26]가 주를 이루고 있으며 이 와 관련된 심리사회적 변인들로 우울 [1,4,5], 부담감 [22], 삶의 질 [13], 대처 [13,26,27] …”
unclassified